Nociceptive capacity of plantar irritating stimulus reduction influences postural control in children, teenagers, and adults. - Marc, Janin; Ceci, Lisandro Antonio; Parreira, Rodolfo Borges (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: Sensory information from vestibular, visual, proprioception, and feet contribute on postural control. Plantar afferent contribution comes from the tactile and nociceptive cues of the plantar sole. Nociceptive capacity of plantar irritating stimulus (NCPIS) is one of the foot problems that induce nociception. Objective: Was to determine the postural impact of sensory input flow modifications induced by foam in people with and without nociceptive plantar irritating stimuli in different ages (children, adolescents, and adults). Method: 120 participants with (NP) and X without (Ct) NCPIS in different age group were evaluated (20 subjects in each age group and conditions). Postural balance assessment was performed during two-legged stance test using a force platform. Postural recoding was performed with eyes open in two conditions: on a hard surface and on a foam surface. The postural balance parameter analyzed was center of pressure area and variance of speed. Results: Area and variance of speed in control group increased, whereas decreased in NP subjects. No differences were observed for mean speed. In the Ct group, nociceptor and mechanoreceptor afferent sensations on foam induced postural variation with more oscillations (area and speed). Conclusion: NCPIS influenced postural control, and this foam neutralization of afferent nociception induced a new sensory organization. Foam surface imitated afferent plantar sensory information, induced postural variation as measured by CoP parameters with increasing postural control in subjects without NCIPS and decreasing postural control in subjects with NCPIS.